Differences in Sexual and Physical Abuse History by Presenting Chief Complaint in an Outpatient Urogynecology Population. Issue 3 (10th March 2023) - Hansbarger, Molly; Ackenbom, Mary; Shepherd, Jonathan P.
Abstract : Importance: One in 3 women experience sexual or physical violence in their lifetimes. Health consequences for survivors are numerous, including urogynecologic symptoms. Objectives: We aimed to determine prevalence and factors that predict a history of sexual or physical abuse (SA/PA) in outpatient urogynecology, specifically whether the chief complaint (CC) predicts a history of SA/PA. Study Design: This cross-sectional study analyzed 1, 000 newly presenting patients to 1 of 7 urogynecology offices in western Pennsylvania from November 2014 to November 2015. All sociodemographic/medical data were retrospectively abstracted. Univariable and multivariable logistic regression analyzed risk factors based on known associated variables. Results: One thousand new patients had a mean age of 58.4 ± 15.8 years with a body mass index (BMI) of 28.8 ± 6.5. Nearly 12% reported a history of SA/PA. Patients with CC of pelvic pain were more than twice as likely to report abuse compared with all other CCs (odds ratio [OR], 2.690; 95% confidence interval [CI], 1.576–4.592). Prolapse was the most common CC (36.2%) but had the lowest prevalence of abuse (6.1%). Nocturia was an additional urogynecologic variable predictive of abuse (OR, 1.162 per nightly episode; 95% CI, 1.033–1.308). Increasing BMI and decreasing age both increased the risk of SA/PA. Smoking conferred the highest likelihood of abuse history (OR, 3.676; 95% CI, 2.252–5.988). Conclusions: Although those with a CC of prolapse were less likely to report abuse history, we recommend routine screening for all women. Pelvic pain was the most common CC among women reporting abuse. Special efforts should be made to screen those at higher risk with complaints of pelvic pain who are younger, smokers, with higher BMI, and with increased nocturia.